2013
DOI: 10.1089/ten.tec.2012.0700
|View full text |Cite
|
Sign up to set email alerts
|

Designing a Multicellular Organotypic 3D Liver Model with a Detachable, Nanoscale Polymeric Space of Disse

Abstract: The design of in vitro models that mimic the stratified multicellular hepatic microenvironment continues to be challenging. Although several in vitro hepatic cultures have been shown to exhibit liver functions, their physiological relevance is limited due to significant deviation from in vivo cellular composition. We report the assembly of a novel three-dimensional (3D) organotypic liver model incorporating three different cell types (hepatocytes, liver sinusoidal endothelial cells, and Kupffer cells) and a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 41 publications
2
51
0
Order By: Relevance
“…Larkin et al reported a more complex model of rat LSEC and Kupffer cells separated by a chitosan-hyaluronic acid polymer layer from collagen embedded primary rat hepatocytes. Under static culture conditions the hepatocytes maintained their phenotype without signs of dedifferentiation [62]. A biodegradable chitosan membrane was also used by Salerno et al for co-culture of human primary hepatocytes with HUVEC, where beneficial effects of the co-culture on hepatocyte albumin production, urea synthesis and drug biotransformation again was reported [63].…”
Section: Discussionmentioning
confidence: 99%
“…Larkin et al reported a more complex model of rat LSEC and Kupffer cells separated by a chitosan-hyaluronic acid polymer layer from collagen embedded primary rat hepatocytes. Under static culture conditions the hepatocytes maintained their phenotype without signs of dedifferentiation [62]. A biodegradable chitosan membrane was also used by Salerno et al for co-culture of human primary hepatocytes with HUVEC, where beneficial effects of the co-culture on hepatocyte albumin production, urea synthesis and drug biotransformation again was reported [63].…”
Section: Discussionmentioning
confidence: 99%
“…In this technique, alternating layers of cationic and anionic polymers are deposited via electrostatic attraction on charged surfaces or on top of cells. LBL has been used with natural and synthetic 31 polyelectrolytes to cover hepatocytes in plate culture 32–35 , and as a seeding layer for hepatocyte co-cultures in microfluidic devices 36,37 . Here, we report the deposition of an ultrathin, pure collagen nanolayer on hepatocytes in microfluidic devices using the LBL technique with methylated and succinylated collagens.…”
Section: Introductionmentioning
confidence: 99%
“…Media was exchanged daily in all models, with constructs cultured for 72 hours. While previous studies have shown that longer culture periods promote increases in hepatic functions, such as albumin and urea synthesis as well as CYP activity [30], we chose to evaluate an early time point in order to establish baseline proteomic measurements in the liver models. Hepatocytes and PEMs were subsequently separated and subjected to processing to peptides that were amenable to bottom-up proteomic analyses.
Fig.
…”
Section: Resultsmentioning
confidence: 99%